Elaboration and characterisation of a miniature soft lactic goat cheese model to mimic a factory cheese. (July 2023) - Baleswaran, Abirami; Couderc, Christel; Reyrolle, Marine; Le Bechec, Mickaël; Daydé, Jean; Tormo, Hélène; Jard, Gwénaëlle
Abstract: Although soft lactic goat cheeses are widely produced in France, there is little information available in the literature about them and no miniature model for this kind of cheese has yet been proposed. In this study, a miniature soft lactic goat cheese model was compared with equivalent factory cheese to use it as a reliable model for this cheese family. The composition of the cheeses was compared at four key stages of the production process using microbiological, physicochemical and Sift-MS volatilome analysis. The compositions of the model and factory cheeses were found to be similar until the ripening step, but some differences were observed on ripened cheeses. Moreover, under carefully monitored laboratory conditions, the variability across batches of the model cheese was reduced. This miniature soft lactic goat cheese could therefore be used as a reliable model to study the aspects of the same cheese type.